The Implementation of the Licensing Service on Public Transport Operational in Tomohon City - Mandagi, Marthinus; Kairupan, Sisca B.; Mantiri, Jeane (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at knowing the implementation of the service on public transport operational license in Tomohon city. Qualitative approach was used in this research and the data were collected by observation, interview and documentation. Based on research finding about the implementation of the service on public transport operational license in Tomohon city, could be concluded that: 1) in registration phase, the management mechanism of public transport operational license was opened to public. 2) in physical inspection of vehicle phase, there was lack of awareness regarding to the operational licensing management of public transport. 3) in retribution payment phase, government did not distinguish the background of society. 4) in the making of license, the equipping of worker (officer), tool and infrastructure were sufficient. 5) in signing phase, the determined procedure had not been yet undertaken well. Based on the conclusion of research finding, constructive suggestions that could be addressed to assist the implementation of the service on operational licensing of public transport in Tomohon city were: 1) The awareness of civil/public transport driver to obey and support the regulation brought on by the government was needed in order to maintain a good relationship between government and society. 2) government was expected to be wiser and more thoughtful in dealing with the problem occurred in signing phase, it should be better if the government (agency chiefs) could reduce the number of external duties and delegated to the vice with regard to the license signing.